Improving systemic delivery of oncolytic virus by cellular carriers - Ziyi Peng; Muhammad Kalim; Yong Lu (Cancer Biology & Medicine)
Oncolytic virotherapy (OVT) is a promising option for cancer treatment. OVT involves selective oncolytic virus (OV) replication within cancer cells, which triggers anti-tumor responses and immunostimulation. Despite promising potential, OVT faces critical challenges, including insufficient tumor-specific targeting, which results in limited tumor penetration and variability in therapeutic efficacy. These challenges are particularly pronounced in solid tumors with complex microenvironments and heterogeneous vascularization. A comprehensive research program is currently underway to develop and refine innovative delivery methods to address these issues to enhance OVT precision and efficacy. A principal area of investigation is the utilization of cellular carriers to enhance the delivery and distribution of OVs within tumor microenvironments, thereby optimizing immune system activation and maximizing anti-tumor effects. This review offers a comprehensive overview of the current strategies that are being used to enhance the delivery of OVs via cellular carriers with the goal of improving the clinical impact of OVT in cancer therapy.